STEMMING BAHASA JAWA MENGGUNAKAN DAMERAU LEVENSHTEIN DISTANCE (DLD) - Aji Prasetya Wibawa; Muhammad Nu’man Hakim (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2021)
Stemming is one of the essential stages of text mining. This process removes prefixes and suffixes to produce root words in a text. This study uses a string matching algorithm, namely Damerau Levenshtein Distance (DLD), to find the basic word forms of Javanese. Test data of 300 words that have a prefix, insertion, suffix, a combination of prefix and suffix, and word repetition. The results of this study indicate that the Damerau Levenshtein Distance (DLD) algorithm can be used for Stemming Javanese text with an accuracy value of 49.6%.